2012
DOI: 10.1002/adma.201203458
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conductive and Strain‐Released Hybrid Multilayer Ge/Ti Nanomembranes with Enhanced Lithium‐Ion‐Storage Capability

Abstract: Highly conductive and hybridized microtubes relying on strain-released ultrathin Ti/Ge bilayer nanomembranes are reported. These hybrid multilayer microtubes show a remarkably enhanced reversible capacity up to 1495 mA h g(-1) with a high first-cycle Coulombic efficiency of 85%, and demonstrate an excellent capacity of ≈930 mA h g(-1) after 100 cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
1
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(117 citation statements)
references
References 36 publications
4
109
1
3
Order By: Relevance
“…In addition, the proposed technology can be extended, and the helical antenna can be prepared in a single fabrication process out of the planar layout, accommodating various functional elements, including energy storage, 46,47 active electronics, 39 and magnetic 48 and fluidic 41 sensorics, hence realizing in vivo smart implants based on multifunctional compact electronics. 49 …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the proposed technology can be extended, and the helical antenna can be prepared in a single fabrication process out of the planar layout, accommodating various functional elements, including energy storage, 46,47 active electronics, 39 and magnetic 48 and fluidic 41 sensorics, hence realizing in vivo smart implants based on multifunctional compact electronics. 49 …”
Section: Resultsmentioning
confidence: 99%
“…After 400 cycles at 40C rate, the capacity was 1000 mAh g À1 . Surprisingly, most studies on Ge anodes have been performed on nano-Ge with dimensions 100 nm [267,[269][270][271] or even 3 nm [272] missing the main interest of the germanium element, presumably by continuity with the prior works on Si where the nano-size was mandatory. In particular, Ge nanowires have been grown by CVD [273], like Si nanowires.…”
Section: Germaniummentioning
confidence: 96%
“…[18][19][20][21][22][23][24][25] Nevertheless, the practical application of Ge is hindered by the pulverization problem caused by the large volume changes during Li insertion/extraction processes, thus leading to the loss of electrical conductivity and consequently a rapid capacity decline upon cycling. [26][27][28][29][30][31] Previously studies have demonstrated that decreasing the Ge particle size into the nanometer range could alleviate the stress produced during Li uptake and release processes and suppress the tendency of the nanostructure to fracture. [32][33][34][35] Moreover, the nanostructure can facilitate the diffusion of Li ion, resulting in high rate capability.…”
Section: Introductionmentioning
confidence: 99%